N-Myristoyltransferases as antileishmanial targets: a piggyback approach with benzoheterocyclic analogues - Luis Otávio Junqueira; Marcela Oliveira Legramanti da Costa; Daniela Gonçales Galasse Rando (Universidade de São Paulo, 2019)
Leishmaniasis is one of the neglected diseases that remain in need for pharmacological alternatives. In this context, N-Myristoyltransferases (NMT) arise as interesting targets to explore since they are involved in the co/post-translational processing of peptides which are responsible for host cell invasion. Studies that consider these enzymes as targets point out the potential of benzoheterocyclic compounds as inhibitors of Candida albicans's N-myristoyltransferase. Here we applied a combination of comparative binding site analysis and molecular docking studies based on a Piggyback approach in the search for new Leishmania major NMT ligands. Our results revealed that NMT enzymes from both pathogens present enough structural similarity to allow extrapolation of the knowledge available from C. albicans studies to develop new L. major NMT inhibitors. Molecular docking studies with benzoheterocyclic analogues indicate the potential of benzothiazole derivatives as L. major NMT ligands, giving rise to a completely new class of chemical compounds to be explored in the development of antileishmanial drugs.